R-carvedilol, a potential new therapy for Alzheimer’s disease - Yao, Jinjing; Chen, S. R. Wayne (Frontiers in Pharmacology, 2022)
For decades, the amyloid cascade hypothesis has been the leading hypothesis in studying Alzheimer’s disease (AD) pathology and drug development. However, a growing body of evidence indicates that simply removing amyloid plaques may not significantly affect AD progression. Alternatively, it has been proposed that AD progression is driven by increased neuronal excitability. Consistent with this alternative hypothesis, recent studies showed that pharmacologically limiting ryanodine receptor 2 (RyR2) open time with the R-carvedilol enantiomer prevented and reversed neuronal hyperactivity, memory impairment, and neuron loss in AD mouse models without affecting the accumulation of ß-amyloid (Aβ). These data indicate that R-carvedilol could be a potential new therapy for AD.